Profil Kesehatan Kerja Nelayan Tangkap di Desa Papela Kecamatan Rote Timur Kabupaten Rote Ndao - Paskalis Marianus Subarjo; Jacob M. Ratu; Agus Setyobudi (Universitas Nusa Cendana, 2021)
Papela Village is one of the coastal villages on Rote Island where most of the population works as fishermen. This work has been carried out by the people of Papela Village for generations. However, health problems caused by fishermen's work and work environment have not received serious attention. This study aims to obtain an overview of the occupational health status of catch fishermen in Papela Village, Rote Timur District, Rote Ndao Regency. This research is a descriptive study with a quantitative approach. A total of 71 people randomly selected were assigned as research respondents. Fishermen's health status is determined based on three parameters, namely anemia status, muscle complaints, and skin diseases. The results showed the occupational health status of catch fishermen in Papela Village as much as 60.6% had a low occupational health status and 39.4% of the people had a high occupational health status. The low health status of fishermen was caused by anemia with a proportion of 26.8%, musculoskeletal complaints with a proportion of 19.7%, and skin disease with a proportion of 38%. It can be concluded that the occupational health status of fishermen in Papela Village is still low and needs to be improved through efforts to minimize the negative influence of the risk factors.